Adaptation of Community Innovation in Stamp Digitalization - Fajarwaty, Ria; Hana Putri , Salsabila; Wempi, J.A (JP (Jurnal Pendidikan) : Teori dan Praktik, 2025)
The rapid digital revolution driven by technological progress has significantly transformed various aspects of daily life, particularly in document authentication and validation. This paper examines the transition from conventional physical stamps to digital stamps (e-stamps) in Indonesia, an innovation developed to modernize administrative processes. Using a qualitative approach within a constructivist framework, the study explores public adaptation to e-stamps by analyzing adoption patterns, digital literacy challenges, and societal perceptions of security, convenience, and effectiveness. Guided by Rogers’ Diffusion of Innovation Theory, the research evaluates the strengths and limitations of this transition through five attributes of innovation: relative advantage, compatibility, complexity, trialability, and observability. Data were collected through literature review, interviews with institutional representatives, and focus group discussions involving participants of diverse ages, professions, and digital literacy levels. The findings indicate that although e-stamps offer notable advantages—such as increased efficiency, security, and accessibility—their adoption is hindered by technical difficulties, user resistance, and limited opportunities for practice. Younger and more technologically proficient groups adapt more readily, whereas older or less digitally skilled individuals face significant barriers. The study underscores the need for comprehensive public education, robust technical support, and targeted outreach programs to strengthen adoption. The insights generated provide valuable guidance for policymakers and implementing agencies in enhancing the rollout and equitable access to e-stamps, thereby supporting Indonesia’s broader digital transformation in public administration.